SISTEM MONITORING UDARA HASIL PEMBAKARAN SAMPAH - Fathonni, Mochammad Cyrilla; Maulana, Eka; Aswin, Muhammad (Jurnal Mahasiswa TEUB, 2024)
Waste incineration is one of the solutions to reduce the amount of waste. This combustion can be useful for breaking down solid waste, but the process of burning waste can produce harmful residual gas emissions. So in this study, a trial was conducted using incinerator technology, an incinerator is a device that functions to burn garbage or waste in solid form and is operated by utilizing combustion technology at a certain temperature. This research was conducted to present a solution by measuring and filteringthe remnants of waste combustion gas emissions which are very dangerous for the human respiratory system. From the description of these problems, a tool is needed that can measure and filter the remnants of waste combustion emission gas. So one way that can be done is by monitoring how bad the levels of CO and CO2 gas contained in the remaining combustion and then binding or filtering these gases using precipitator technology so that the air that will come out of the remains of dangerous combustion that can disturb humans can be reduced. Keywords: Waste incineration, incinerators, precipitators, CO gas, and CO2 gas.